2022
DOI: 10.3389/fanim.2021.806967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Vitamin D3 and Ultraviolet B Light on Growth Performance, Blood Serum Parameters, Gut Histology, and Welfare Indicators of Broilers

Abstract: Stressors are commonly encountered by all farmed species, including chickens, but the impact of these stressors on the animal and their productivity can be influenced by the environmental conditions in which they are kept. This study investigated the effects of dietary vitamin D3 (vitD3) and ultraviolet light (UVB) on growth performance, organ weight, serum corticosterone levels (CORT), serum 25-hydroxy vitamin D (25-OH-D3) status, gut histology, and welfare indicators of broiler chickens challenged with socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…For example, DUV-LEDs are suitable for the production of vitamin D 3 . In human skin, vitamin D 3 production depends on several factors, including the person’s age, the time of day, the latitude and altitude, the season, the area of exposure, and the degree of skin pigmentation, with ultraviolet-B (UVB) wavelengths between 290 and 300 nm being most efficient [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Kalajian et al [ 14 ] found that light at a wavelength of 293 nm was 2.4 times more efficient at producing vitamin D 3 in human skin than light from the sun was, as measured according to the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DUV-LEDs are suitable for the production of vitamin D 3 . In human skin, vitamin D 3 production depends on several factors, including the person’s age, the time of day, the latitude and altitude, the season, the area of exposure, and the degree of skin pigmentation, with ultraviolet-B (UVB) wavelengths between 290 and 300 nm being most efficient [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Kalajian et al [ 14 ] found that light at a wavelength of 293 nm was 2.4 times more efficient at producing vitamin D 3 in human skin than light from the sun was, as measured according to the exposure time.…”
Section: Introductionmentioning
confidence: 99%